EXPLORING EFFECTIVE TEACHER’S INTERACTION STRATEGIES IN EFL CLASSROOM DISCOURSE : A CASE STUDY OF SECONDARY EDUCATION IN PALOPO - Alfianty Tadjuddin (Universitas Andi Djemma, 2019)
This study explored the types and the impact of teacher’s strategies used by an effective teacher in EFL classroom discourse based on the theory of Walsh (2011). The researcher applied a positive case study method by a single participant to examine the phenomena of interaction strategies used by an effective teacher in EFL classroom discourse. The participant was an English teacher of SMA Negeri 3 Palopo, who has chosen by using purposive sampling technique. In collecting the data, the researcher conducted observations by using video recorder to find out teacher’s utterance and performance in the classroom. Interview was used as support the data to know students’ responses toward teacher’s strategies in EFL classroom. Meanwhile, document was used to find out the students’ achievement by final examination scores. The results showed that there were four types of teacher’s strategies used by an effective teacher in EFL classroom discourse namely interaction management, questioning, feedback, and repairing. There were positive impacts of the implementation of teacher’s strategies toward students’ achievement in the learning process. Document of final examination scores showed that most of students had good achievement and they have high motivation in learning English as Foreign language. Furthermore, the researcher also found the new strategy that occurred by an effective teacher, namely Reinforcement Motivational Practice.